Systematic Literature Review and Meta-Analysis of Renal Function in Human Immunodeficiency Virus (HIV)-Infected Patients Treated with Atazanavir (ATV)-Based Regimens. - Sandrine Cure; Florence Bianic; Caroline Espinas; Helene Hardy; Lisa Rosenblatt; Timothy Juday (PLoS ONE)
Some HIV antiretroviral therapies (ART) have been associated with renal toxicities, which become of increasing concern as HIV-infected patients age and develop comorbidities. The objective of this study was to evaluate the relative impact of atazanavir (ATV)-based regimens on the renal function of adult patients with HIV. We conducted a systematic literature review by searching PubMed, EMBASE, Cochrane library, and the CRD from 2000 until March 2013. Major HIV-related conferences occurring in the past two years were also searched. All randomized clinical trials and large cohort studies assessing renal function in treatment-naïve and/or treatment-experienced HIV patients on ATV-based regimens were included. Fixed-effect mixed-treatment network analyses were carried out on the most frequently reported renal outcomes. 23 studies met the inclusion criteria, and change in estimated glomerular filtration rate (eGFR) from baseline to 48 weeks was identified as the main outcome. Two networks including, respectively, six studies (using the Cockcroft-Gault method) and four studies (using MDRD and CKD-EPI) were analysed. With CG network, ATV/r + TDF/FTC was associated with lower impact on the decline of eGFR than ATV/cobicistat + TDF/FTC but with higher decrease in eGFR than ATV/r + ABC/3TC (difference in mean change from baseline in eGFR respectively +3.67 and -3.89). The use of ATV/cobicistat + TDF/FTC led to a similar decline in eGFR as EVG/cobicistat/TDF/FTC. With respect to third agents combined with TDF/FTC, ATV/r had a lower increase in eGFR in comparison to EFV, and no difference was shown when compared to SQV/r and DRV/r. The effect of ATV-based regimens on renal function at 48 weeks appears similar to other ART regimens and appears to be modest regardless of boosting agent or backbone, although TDF containing backbones consistently leads to greater decline in eGFR.